Kinerja Dinas Perindustrian dan Perdagangan Sumatera Utara Dalam Memperkuat Industri Kecil Menengah di Kota Medan - Siska Junianti; Teguh Haikal Fitra; Muhammad Riduan; Zainarti Zainarti (Khidmatussifa: Journal of Islamic Studies, 2023)
The small business sector is one industry that is essential to the economy. Some of them take in workers, which greatly boosts local income. comparable to what occurred in Medan. One of the biggest cities in Indonesia is Medan, which ranks third after Jakarta and Surabaya. It cannot be separated from the difficulties SMEs face, though. There are many difficulties, such as a lack of tools and knowledge. In order to support the growth of small and medium-sized businesses, the Ministry of Industry and Trade of the city of Medan has implemented various performance and policy measures. The research methodology of choice is qualitative. The author ran an apprenticeship program at the North Sumatra province's industry and commerce office to gauge how successfully the government was handling this issue. According to the study's findings, specific instances of this performance include: 1) providing funds, 2) maintaining and improving infrastructure, 3) providing business information, 4) fostering networking relationships, 5) issuing business licenses, 6) offering business opportunities, 7) enhancing businesses, and 8) providing assistance to the community. Keywords : Small and Medium-Sized Enterprises, Performance, and Medan City